Answer:
Subtract equation 1 from equation 2
Explanation:
Solve the following system:
{3 x + 4 y = 12 | (equation 1)
3 x = 2 y - 8 | (equation 2)
Express the system in standard form:
{3 x + 4 y = 12 | (equation 1)
3 x - 2 y = -8 | (equation 2)
Subtract equation 1 from equation 2:
{3 x + 4 y = 12 | (equation 1)
0 x - 6 y = -20 | (equation 2)
Divide equation 2 by -2:
{3 x + 4 y = 12 | (equation 1)
0 x+3 y = 10 | (equation 2)
Divide equation 2 by 3:
{3 x + 4 y = 12 | (equation 1)
0 x+y = 10/3 | (equation 2)
Subtract 4 × (equation 2) from equation 1:
{3 x+0 y = (-4)/3 | (equation 1)
0 x+y = 10/3 | (equation 2)
Divide equation 1 by 3:
{x+0 y = (-4)/9 | (equation 1)
0 x+y = 10/3 | (equation 2)
Collect results:
Answer: {x = -4/9 , y = 10/3